Masculine and Feminine Characters of Female Figures Found in Nusa Tenggara Timur Fairy Tales (Martabat: Jurnal Perempuan dan Anak, 2020)
This research was begun by basic question, “Is it true that past patriarchal society in NTT created their mindset that women are destined to have a feminine character within themselves?” By then, this study aims to describe the comparison of masculine characters and feminine characters of female figures found in NTT fairytales. The data sources of this research are 9 (nine) local fairytales of NTT which figured out a female figure as the main character. The technique of collecting the data was adopted by researchers through literature study. The data analysis includes the stages of reading, identifying, classifying, interpreting, and presenting the results of analysis. The results showed that the grouping of masculine and feminine characters displayed in fairy tales is very biased. The lines of character identification that exist for men and women are broad, not strict. The data in fairy tales that show masculine characters in female figure is 69%, while the data showing feminine characters is 31%. Based on the results of the analysis, it can be concluded that women, in NTT fairytales, are described as possessing a masculinity. In many ways, female characters are depicted as the same characteristics as men, such as achievement, relationship, independence, courage, and resistance to oppression.